CURRENT STATE OF DEVELOPMENT OF MANAGEMENT ACTIVITIES OF THE DIRECTOR OF THE PRE-CARE INSTITUTION - Pulatovna, Maraimova Mukhtabar (Journal of Higher Education and Academic Advancement, 2024)
This article presents the current situation, problems and solutions in the management of preschool educational organizations